Multivariate analysis of mental and physical load components in sinus arrhythmia scores - Lee, D H; Park, K S (Ergonomics, 1990)
In many studies on the relationship between mental load and sinus arrhythmia (SA) scores the effect of minor motor actions inevitably accompanying light work has been disregarded. However, because the chemoreceptors for muscle cell activities are directly coupled with the heart rate (HR) control centre in the brain, even minor motor actions can influence SA. In this study mental and physical loads were scored respectively by information processing and finger tapping rates. Percentage changes in SA and HR above resting levels were scored from the heart beat intervals of the subjects. According to a multivariate regression analysis of SA scores on mental and physical load components, an increase in mental load decreased SA, but did not increase HR significantly. An increase in physical load decreased SA and increased HR significantly.